Keseimbangan Pasar Uang - Bella Permata Sari; Devika Putrani; Rama Maulana; Vemas Praditya Pangestu; Suci Hayati (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to examine the concept of money market equilibrium and the elements that influence it in the context of an open economy. Money market equilibrium occurs when the need for money is equal to the amount available at a certain interest rate. This study uses a quantitative descriptive methodology using secondary data from national financial reports and monetary indicators. The results of the analysis show that interest rates and national income are key variables that influence money market equilibrium. In addition, monetary policy implemented by financial authorities plays an important role in maintaining money market stability. These findings have a significant influence on the formulation of macroeconomic policies, especially in maintaining price stability and encouraging economic growth through efficient liquidity management.